2014
DOI: 10.1016/j.astropartphys.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Limiting superluminal electron and neutrino velocities using the 2010 Crab Nebula flare and the IceCube PeV neutrino events

Floyd W. Stecker

Abstract: The observation of two PeV-scale neutrino events reported by Ice Cube allows one to place constraints on Lorentz invariance violation (LIV) in the neutrino sector. After first arguing that at least one of the PeV IceCube events was of extragalactic origin, I derive an upper limit for the difference between putative superluminal neutrino and electron velocities of ≤∼ 5.6 × 10 −19 in units where c = 1, confirming that the observed PeV neutrinos could have reached Earth from extragalactic sources. I further deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 42 publications
1
60
1
Order By: Relevance
“…The observation of these neutrinos with PeV energies implies that this threshold energy lies above 1 PeV, leading to stringent limits on isotropic Lorentz violation of dimension = 4, 6, 8, and 10 [81]. Similar studies for the case = 4 can be found in [93,94].…”
Section: 3cerenkov Radiationsupporting
confidence: 52%
“…The observation of these neutrinos with PeV energies implies that this threshold energy lies above 1 PeV, leading to stringent limits on isotropic Lorentz violation of dimension = 4, 6, 8, and 10 [81]. Similar studies for the case = 4 can be found in [93,94].…”
Section: 3cerenkov Radiationsupporting
confidence: 52%
“…In other words: Is there any constraint on the velocity of the superluminal electron? For an answer to this question, see, for example, Stecker (2014) who studies and discusses the limits on superluminal electron and neutrino velocities.…”
Section: Calculation Of the Expectation Value Of The Overall Linear Vmentioning
confidence: 99%
“…Noting that the superluminal neutrinos will produce electron-positron pairs and loss their energy rapidly [26], very stringent constraints on LIV have been obtained for superluminal neutrinos [27][28][29]. We here consider the constraints for subluminal neutrino LIV.…”
mentioning
confidence: 99%